Pengaruh Penerimaan Pajak Reklame dan Pajak Walet terhadap Pendapatan Asli Daerah Kota Baturaja (Studi Kasus BAPENDA) - Fernando, Muhammad Rizky; Aini, Hasiatul; Dona, Eka Meiliya; Yulitiawati, Yulitiawati (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study aimed to determine the influence of advertisement tax and swallow's nest tax on the local revenue of Baturaja City (Case Study of BAPENDA), both partially and simultaneously. This study used quantitative research methods. The data used in this study were secondary data sourced from the BAPENDA office in Kab Oku.The analysis tool used in this study was Multiple Linear Regression. The results of this study showed that partially, the advertisement tax variable did not have a significant influence on local revenue. Meanwhile, the swallow's nest tax variable had a significant influence on local revenue. The coefficient of determination (R square) was 0.610, which meant that the contribution and influence of the independent variables, namely advertisement tax and swallow's nest tax, on the dependent variable, namely the local revenue of Baturaja City, was 61.0%, while the remaining 39.0% was influenced by other factors such as local taxes on hotels, land and buildings, restaurants, entertainment, etc Keywords:Local Revenue, Advertisement Tax, Swallow's Nest Tax